Pengaruh Inflasi, Jumlah Uang Beredar, Kurs Dan Suku Bunga SBI Terhadap Indeks Harga Saham Di Jakarta Islamic Index (JII) Periode 2017–2022 - Sari, Nurma; Hanif, Muhammad Hanif Fariswan; Saputra, Mulia (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
This study aims to analyze the influence of inflation, money supply, exchange rate and SBI interest rates on the stock price index in the Jakarta Islamic Index for the period 2017 – 2022. The data used in this study is secondary data that is quantitative in nature consisting of monthly inflation data, money supply, changes in exchange rates, SBI interest rates and the Jakarta Islamic Index. The analysis used is Multiple Linear Regression. The results of the study show that partially the inflation and interest rate variables have a significant positive effect on the stock price index in the Jakarta Islamic Index, while the exchange rate variable partially has a significant negative effect on the stock price index in the Jakarta Islamic Index and the variable of the money supply does not partially affect the stock price index in the Jakarta Islamic Index. Then simultaneously, inflation variables, money supply, exchange rate and SBI interest rate have a significant effect on the stock price index in the Jakarta Islamic index. The results of the study explain the importance of maintaining the stability of foreign exchange rates so that they are not too high, which has an impact on the weakening of stocks.